Place-based ethnomathematics for early numeracy: Geometric representations from the tugu pahlawan monument in Surabaya - Yustitia, Via; Kintoko, Kintoko; Pamungkas, Megita Dwi; Wijayanti, Septiana (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to understand how the cultural elements of Surabaya’s Tugu Pahlawan Monument can be used to introduce basic numeracy in primary school, especially concepts related to plane geometry. The goal is to show that cultural landmarks can offer real and relatable examples for young learners. Method: The research was conducted through a qualitative ethnographic approach. The researcher observed the monument directly, spoke with on-site guides and staff who were familiar with its history, and documented various architectural and visual features. All information gathered from notes, photographs, and short interviews was analyzed using the Miles and Huberman framework to identify patterns that relate to mathematical ideas. Findings: The study found that many parts of the monument display clear geometric forms. These include rectangles, squares, circles, triangles, trapezoids, rhombuses, and even a ten-sided figure. Such shapes appear in the floor patterns, plaques, murals, decorative ornaments, museum structures, and the wheels of military displays. Each of these elements can be directly connected to geometry topics taught in primary classrooms. Significance: The findings highlight the potential of local heritage as a meaningful resource for mathematics education. When students see that the shapes they learn in class appear in a monument tied to their own city’s history, mathematical concepts become easier to grasp and more engaging. This approach supports early numeracy while also helping learners build a stronger connection to their cultural environment.